1974
DOI: 10.2118/4096-pa
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Capillary-Pressure Functions and the Influence of Connate Water

Abstract: Drainage capillary-pressure functions oi reservoir rock-fluid-fluid systems OCTOBER. 1974 .497 SOCIETY OF PET ROLS1" M ES GIXKERS JO I R\,\L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(62 citation statements)
references
References 0 publications
5
56
0
Order By: Relevance
“…They observed that the presence of connate water is critical for achieving very low oil residual saturations during gravity drainage floods, under high gas-oil capillary pressures, irrespective of whether or not the oil spreads on water in the presence of gas. Interestingly, Dumore and Schols (1974) attribute the achievement of low residual oil saturations to possible 'film flow'. This appears to contradict their previous inference that the oil spreading need not occur in presence of gas, and that the contribution of oil from film flow in secondary gas caps is negligible.…”
Section: Gravity Drainage Fundaments and Traditional Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…They observed that the presence of connate water is critical for achieving very low oil residual saturations during gravity drainage floods, under high gas-oil capillary pressures, irrespective of whether or not the oil spreads on water in the presence of gas. Interestingly, Dumore and Schols (1974) attribute the achievement of low residual oil saturations to possible 'film flow'. This appears to contradict their previous inference that the oil spreading need not occur in presence of gas, and that the contribution of oil from film flow in secondary gas caps is negligible.…”
Section: Gravity Drainage Fundaments and Traditional Modelsmentioning
confidence: 99%
“…Reservoir water saturation, both connate (bound) and free (mobile), has been found to influence the oil recovery characteristics of many enhanced recovery processes (Dumore and Schols, 1974;Hagoort, 1980;. From a gas injection point of view, oil recovery rates (and efficiency), especially during the injection of a watersoluble solvent (such as CO 2 ), have been found to be directly related to the free water saturation in the reservoir .…”
Section: Effect Of Mobile and Connate Water Saturationmentioning
confidence: 99%
See 2 more Smart Citations
“…The free-fall gravity drainage, which is representative of gas injection into a depleted fractured reservoir, has been investigated by Le~erett,~" Stahl et a p 2 Cardwell and Pars0ns,2'~ Nenniger and St~rrow,"~ Templeton and Niel~en;~' Dumore and Schols, 260 Unlike forced gravity drainage, free-fall gravity drainage cannot be modeled using a Buckley-Leverett approach because flow rate is not prespecified. A survey of the literature reveals four mathematical models that have been developed for describing the process of free-fall gravity drainage of equilibrium fluids.…”
Section: Stensen Et ~1 ~~~mentioning
confidence: 99%